The length of AZT consumption and homocysteine levels are protective factors of macrocytic anemia among adult HIV-infected patients: A case-control study in Central Java Province, Indonesia (Bangladesh Journal of Medical Science, 2020)
Objective: Macrocytic anemia (MA) is the most common type of anemia in adult HIV-infected patient on azidothymidine (AZT) regimen. The common causes of MA are vitamin B12 and folate deficiency, marked by homocysteinemia. AZT consumption causes homocysteinemia is still controversial. This study aimed to determine the role of AZT consumption and homocysteinemia in developing MA.Materials and Methods: This was a case-control study involving adult HIV-infected patient who administered AZT in 12 health care facilities in Central Java Province, Indonesia. Sociodemographic data were obtained through interviews and medical records, while laboratory data included hemoglobin level and mean corpuscular volume (MCV) were measured using the automatic hematology analyzer. Homocysteine level was measured using immunoassay. WHO references was used to diagnose anemia. Macrocytic was determined when MCV >96 fl. The cut-off homocysteinemia was >10 μmol/L. Length of AZT consumption was classified into ≤6 months and >6 months. Data were analyzed using multivariate logistic regression test.Results: The population of this study was 503 adult HIVinfected on AZT regimen. In total, there were 116 subjects (age mean±SD: 41,9±9,4) who had MA and 116 controls (age mean±SD: 36,2±8,3) without anemia. Prevalence of anemia was 29.4% and the majority (78.4%) had MA. The odds of having MA among adult HIV infected patient on AZT regimen > 6 months was 0.25 times compared to patients who were on AZT regimen ≤6 months (95% CI 0.08-0.72, p=0.011), homocysteinemia was protective factor of MA (OR 0.43,95% CI 0.24-0.79, p=0.006).Conclusion: The length of AZT consumption >6 months and homocysteinemia are protective factors of MA among adult HIV-infected patient.Bangladesh Journal of Medical Science Vol.19(4) 2020 p.638-645